2018
DOI: 10.1016/j.neurobiolaging.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

GABA levels and measures of intracortical and interhemispheric excitability in healthy young and older adults: an MRS-TMS study

Abstract: Edited magnetic resonance spectroscopy (MRS) and transcranial magnetic stimulation (TMS) have often been used to study the integrity of the GABAergic neurotransmission system in healthy aging. To investigate whether the measurement outcomes obtained with these 2 techniques are associated with each other in older human adults, gamma-aminobutyric acid (GABA) levels in the left sensorimotor cortex were assessed with edited MRS in 28 older (63-74 years) and 28 young adults (19-34 years). TMS at rest was then used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 74 publications
5
53
1
Order By: Relevance
“…Fujiyama et al [55] showed that a reduced capacity of GABA-mediated inhibition has a clear impact on short-interval intracortical inhibition during response preparation for a motor exercise. These findings were more recently supported by those of other authors [59][60][61][62][63][64]. Nonetheless, the effect of ageing on the GABAergic system has raised many questions and many discrepancies have emerged in the literature as recently described in a comprehensive review [65].…”
Section: Supraspinal Age-related Adaptationssupporting
confidence: 60%
“…Fujiyama et al [55] showed that a reduced capacity of GABA-mediated inhibition has a clear impact on short-interval intracortical inhibition during response preparation for a motor exercise. These findings were more recently supported by those of other authors [59][60][61][62][63][64]. Nonetheless, the effect of ageing on the GABAergic system has raised many questions and many discrepancies have emerged in the literature as recently described in a comprehensive review [65].…”
Section: Supraspinal Age-related Adaptationssupporting
confidence: 60%
“…With aging, excitability and the capability to modulate excitability seems to decrease, causing motor deficits in older adults (Bhandari et al, ). Interestingly, current studies show that TMS measures of GABAergic inhibition are not correlated with GABA concentrations obtained by MRS (Dyke et al, ; Hermans et al, ; Mooney, Cirillo, & Byblow, ; Stagg et al, ; Tremblay et al, ). This appears to suggest that MRS and TMS investigate distinct mechanisms: whereas MRS is thought to reflect the inhibitory tone of a certain brain region, TMS targets the GABAergic synaptic transmission (Dyke et al, ; Stagg et al, ; Tremblay et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…With advancing age, there are multi-faceted declines in motor performance as well as changes in cortical inhibition (Fling, Kwak, Peltier, & Seidler, 2012;Hermans et al;Hortobágyi, del Olmo, & Rothwell, 2006;Oliviero et al, 2006;Papegaaij, Taube, Hogenhout, Baudry, & Hortobágyi, 2014;Peinemann, Lehner, Conrad, & Siebner, 2001;Pitcher, Ogston, & Miles, 2003). Transcranial magnetic stimulation (TMS) offers a non-invasive method of studying the inhibitory capacity of the motor cortex believed to reflect excitation and inhibition of gammaaminobutyric acid (GABA) or GABA-ergic cortical circuits (Bhandari et al, 2016;Cash et al, 2017;Di Lazzaro et al, 2000;Kujirai et al, 1993;Lazzaro et al, 1998;Ziemann, Lönnecker, Steinhoff, & Paulus, 1996).…”
Section: Introductionmentioning
confidence: 99%